PENGARUH PERBEDAAN UMPAN TERHADAP HASIL TANGKAPAN RAJUNGAN (PORTUNUS PELAGICUS) DENGAN MENGGUNAKAN ALAT TANGKAP BUBU (TRAP NET) PERAIRAN TELUK GERUPUK: The Influence Of Differences On The Catch Crab (Portunus Pelagicus) By Using Bubu Catching Tools (Trap Net) Waters Of Gerupuk Bay) - Hambali, Lalu; Kotta, Raismin; Rahmawati, Aryani; Sukmaring Kalih, L.A.T.T.W. (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The purpose of this study was to determine the effect of different types of bait on crab (Portunus pelagicus) catches in the waters of Gerupuk Bay and to find out which type of bait is more effective for catching blue crab (Portunus pelagicus) from the three types of bait to be used. The method used in this research is the experimental method. This method conducted research on the effect of different crab trap baits on crab catches. The number of catches obtained during the study was 283 crabs (Portunus pelagicus) with an average of 70.75 consisting of X1 with 115 trash fish baits, X2 with 68 sea eel baits and X3 with 100 kuniran fish baits. tail